Violence and identity in "A vitoria do perdedor” - Vilavedra Fernández, Dolores (Madrygal. Revista de Estudios Gallegos, 2014)
This article’s purpose is to analize violence as a vector for elaborating the individual identity of the protagonist of the novel A vitoria do perdedor by Carlos G. Reigosa, and to demonstrate it’s functionality in a narrative context that is presented largely as a field for moral reflexion.